Risk factors for recurrent preterm birth in multiparous Utah women: a historical cohort study. Issue 7 (19th February 2013) - Simonsen, SE; Lyon, JL; Stanford, JB; Porucznik, CA; Esplin, MS; Varner, MW
<x xml:space="preserve">Abstract</x> Objective To describe risk factors for recurrent preterm birth (PTB) in the second and third birth. Design Historical cohort study. Setting Utah, USA. Population Women who had their first three singleton live births in Utah between 1989 and 2007 and a preterm first or second birth were included. Methods Maternally linked birth records were used. Multivariable‐adjusted risk ratios were calculated for recurrent PTB. Results were stratified by spontaneous and indicated PTB and by pattern of birth outcomes. Main outcome measures Risk ratios and 95% confidence intervals for risk factors for recurrent PTB. Results Among women with PTB in their first or second live birth, recurrent PTB occurred in 21% of second live births (n = 1011/4805) and 22% of third live births (n = 1872/8468). Risk factors for recurrence included short inter‐pregnancy interval, underweight prepregnancy body mass index, pre‐existing maternal medical conditions, history of PTB at 28–32 weeks of gestation (versus 33–36 weeks), the presence of a fetal anomaly, and young maternal age. Risk factors for spontaneous, but not indicated PTB included young maternal age and less than appropriate gestational weight gain. Risk factors also varied in women experiencing a first versus second recurrence in their third birth. Conclusions Risk factors may vary by the clinical subtype of the most recent PTB and the pattern of term and preterm outcomes across births 1–3; some of the risk factors identified in this study may be modifiable through interventions targeted at women in the inter‐conception period.